Prospects of teaching pediatrics to english-speaking students at the faculty of medicine and public health of the International Humanitarian University - Nikitina, N. O.; Kukushkin, V. N (Одеса, 2022)
Pediatrics is one of the basic disciplines for laying the foundation for the clinical thinking of a future doctor. The purpose of our work was to substantiate the prospects for teaching Pediatrics to English-speaking students at the Faculty of Medicine and Public Health of the International Humanitarian University. The opportunities for teaching of Pediatrics to foreign English-speaking students are fully provided by creating an information and material base in the form of traditional training in the clinic with the integrated use of modern innovative educational and training technologies.
Nikitina N. O. Prospects of teaching pediatrics to english-speaking students at the faculty of medicine and public health of the International Humanitarian University / N. O. Nikitina, V. N. Kukushkin // Сучасні проблеми фармакології, косметології та аромології : матеріали Х наук.-прак. конф., присвяченій 165-річчю з дня народження професора Яківа Юлійовича Бардаха (1857 — 1929), видатного українського лікаря, мікробіолога, бактеріолога, засновника першої в Одесі і Україні станції швидкої медичної допомоги, та Дню Фармацевта (м. Одеса, 23 вересня 2022 р.). – Одеса: Міжнародний гуманітарний університет, 2022. – С. 53-57.
Keywords: pediatrics; education; students; methods of teaching